The Use of Modern Technologies and Its Impact on The Estimation of Surface Water Flow to Choose the Optimal Sites for Water Collecting in The Wadi Kaifah in The Desert of Iraqi’s Jazeera - Al-Shabani, Mohammed Musa Hammadi (Al-Adab Journal, 2021)
The Paper deals with the study of mechanisms for selecting suitable sites for water collecting, due to their importance for the area in which the Wadi Kaifahah basin is located within the borders of the Jazirah desert, which is characterized by drought and the fluctuation of its rainfall from one season to another. The selection of watershed sites was based on the US Soil Conservation hypothesis (SCS-CN) to estimate the volume of surface runoff through a set of indicators represented by finding the relationship between the types of land cover and the types of hydrological soils to measure the nature of the valley surface for permeability and infiltration depending on remote sensing techniques and systems. Geographical information (GIS), as the (CN) values ​​ranged between (77-91) showed that it has adequate surface runoff, and then estimating the depth of runoff (Q) for the valley basin to estimate the annual volume of runoff (QV), which reached its lowest value. It has (181400 m3) and its highest (21150800 m3), and finally it reached to determine the four most suitable sites for the construction of dams for the watersheds based on the topography of the area and the results of the (SCS-CN) method.